High-Ability Influencers? The Heterogeneous Effects of Gifted Classmates - Simone Balestra; Aurélien Sallin; Stefan C. Wolter (Institute of Labor Economics (IZA), 2020)
This paper examines how exposure to students identified as gifted (IQ ≥ 130) affects achievement in secondary school, enrollment in post-compulsory education, and occupational choices. By using student-level administrative data on achievement combined with psychological examination records, we study the causal impact of gifted students on their classmates in unprecedented detail. We find a positive and significant effect of the exposure to gifted students on school achievement in both math and language. The impact of gifted students is, however, highly heterogeneous along three dimensions. First, we observe the strongest effects among male students and high achievers. Second, we show that male students benefit from the presence of gifted peers in all subjects regardless of their gender, whereas female students seem to benefit primarily from the presence of female gifted students. Third, we find that gifted students diagnosed with emotional or behavioral disorders have zero-to-negative effects on their classmates' performance, a detrimental effect more pronounced for female students. Finally, exposure to gifted students in school has consequences that extend beyond the classroom: it increases the likelihood of choosing a selective academic track as well as occupations in STEM fields.
Keywords: I21; I24; I26; J24; 330; gifted students; peer quality; gender; math; peer effects